Unblinding at disease progression in double-blinded randomized controlled cancer drug clinical trials: A controversy requires more attention - Dawei, Wu; Shuangman, Miao; Huiyao, Huang; Dandan, Cui; Yu, Tang; Ning, Li (Frontiers in Medicine, 2022)
Unblinding at disease progression in double-blinded randomized controlled cancer drug clinical trials is ethical to the patient by ensuring optimal subsequent treatment, but the effect of study treatment on overall survival may be confounded. The views of science and ethics in this issue are controversial and the unblinding procedures should be well-designed. In real world settings, a lack of use of this unblinding process in protocol was observed in the analysis of 134 double-blind randomized controlled anticancer drug clinical trials conducted in China from 2018 to 2021. Unblinding at disease progression was allowed in only 26 (18.2%) trials. Among them, Only 9 (34.6%) trials involved patient-level unblinding. None of the 134 included trials accounted for the risk of blind-maintenance after disease progression. Based on the analysis and case studies, we believe that unblinding at disease progression should be stated in the protocol when the treatment assignment directly affected the choice of subsequent regimen, in which the drug category, control group design, standard of care of further-line therapy and primary endpoint together play a role. When unblinding at disease progression is adopted, the sensitivity analytics are recommended to understand the true effect of study drug on overall survival. The notification of treatment allocation after unblinding and the informed consent also require attention. A decision-making framework is established to help understand this controversy, which should be carefully discussed by the investigator and the sponsor.